Recurrent meningioma of the scalp after 13 years. (7th July 2016) - Ashmore, Daniel Lee; Clancy, Rachel; Chumas, Paul D
Abstract : Meningiomas represent some of the most common types of tumour of the central nervous system. They are considered benign, with ∼1 in 1000 known to metastasise. We report a case of recurrent meningioma of the scalp 13 years following craniotomy to treat the primary. The recurrent tumour of the scalp was eventually excised 5 years later and the defect closed with an anterolateral thigh free flap in a joint procedure between the neurosurgeons and plastic surgeons. Histology of the scalp lesion confirmed a WHO grade I meningioma. Although a number of explanations for recurrent scalp meningiomas exist, the precise role of isolated genetic defects in scalp meningiomas is incomplete. The scalp meningioma in this case consisted of a complex karyotype suggestive of more aggressive disease. This case emphasises that cytogenetics may play a greater role in identifying more aggressive tumours than histology alone.